Hirsutism and Quality of Life of Women in Tertiary Care Center in Eastern Nepal - Maharjan, J.; Agrawal, S.; Marahatta, S. (Kathmandu University Medical Journal, 2022)
Background Hirsutism is excess terminal hair growth in women at androgen-dependent sites of the body and it has great impact on psychological and social aspects of their lives, thus affecting their quality of life (QoL). Several studies assessing the quality of life in hirsute women could be found in world literature but none in Nepalese literature. So, this study was undertaken for the assessment of the impact of hirsutism on the quality of life in Nepalese women.Objective To assess the effect of hirsutism on quality of life of women in a tertiary center of Eastern Nepal and its association with various socio-demographic and clinical parameters.Method A cross-sectional questionnaire-based study was conducted in 49 participants aged 10 to 49 years at the Department of Dermatology, B.P. Koirala Institute of Health Sciences. Clinically diagnosed hirsute females with modified Ferriman-Gallwey (mFG) score > 8, were enrolled and asked to fill Dermatology Life Quality Index (DLQI) questionnaire in the Nepalese version.Result More than 57.2% of the study population was of age 20 to 29 years with a mean of 27.76±8.08 years. The mean Dermatology Life Quality Index score was 7.78±4.95. The moderate effect was seen in the majority of participants (36.7%) with a predominant effect upon aspects of life like daily activities and symptoms and feelings. Participants with higher mF-G score (22.15±3.82) had a very large effect on their quality of life. Younger unmarried women with a school education and having a longer duration of hirsutism were found to have a higher effect upon their quality of life. However, the association was not statistically significant.Conclusion Hirsutism had affected the quality of life moderately with predominant effect upon aspects like daily activities and symptoms and feelings. No significant association was elicited between severity of hirsutism and its effect on quality of life from our study.